The silver locket - Harrison, Paula; Artful Doodlers Ltd. (New York : Scholastic Inc., 2014)
In the kingdom of Taldonia for the Autumn Ball, Rosalind and the other princesses love playing with an adorable puppy name Patch. When a misunderstanding turns into an argument, Rosalind sets off on her own. But when Patch is dognapped, Rosalind needs the other Rescue Princesses to help save Patch.
3.
2-3.
Keywords: Princesses -- Juvenile fiction; Dogs -- Juvenile fiction